IPO Activity in Selected European Capital Markets Between 2012 And 2022 - Daniela SERBAN (COJOCARU) (Communications of International Proceedings, 2023)
This research paper analyses the IPO activity across 8 European countries after the financial crisis from 2012 to 2022. The research focused on individual stock exchanges, rather than conglomerates, with the possibility to link it to the macroeconomic and country-specific indicators. This paper sets grounds for broader research on IPO determinants in the context of analysing capital markets developments and the triggers for capital demand. As the primary role of capital markets is to channel funds between investors and companies or entities seeking financing, understanding the demand for capital is essential in further research on the role of capital markets within national economies. The driver of the research is the European Commission Study in 2020 showcasing the decline of public markets, mainly in Europe, and a negative trend of listings in Europe.
Keywords: Stock Markets; Initial Public Offerings; Macroeconomic Development; European Stock Markets